2014
DOI: 10.1155/2014/696107
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis in Human Multiple Myeloma Cell Lines by Ebselen via Enhancing the Endogenous Reactive Oxygen Species Production

Abstract: Ebselen a selenoorganic compound showing glutathione peroxidase like activity is an anti-inflammatory and antioxidative agent. Its cytoprotective activity has been investigated in recent years. However, experimental evidence also shows that ebselen causes cell death in several cancer cell types whose mechanism has not yet been elucidated. In this study, we examined the effect of ebselen on multiple myeloma (MM) cell lines in vitro. The results showed that ebselen significantly enhanced the production of reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 50 publications
5
25
0
Order By: Relevance
“…Although toxic effects of this drug were unexpected, because the selenium in ebselen is not released, is not bioavailable and ebselen metabolites are excreted in bile and urine, 29 experimental evidence shows that ebselen causes cell death in several cancer cell types, including AR42J cells. 8,9 The concentrations of ebselen that we have employed fall within the range of concentrations employed by others, which vary between 1 and 40 μM, and have reported protective effects of the compound. 30,31 However, previous studies carried out in our laboratory have shown that ebselen may cause damage to the cells.…”
Section: Effect Of Ebselen On Mitogen-activated Protein Kinasesmentioning
confidence: 86%
See 1 more Smart Citation
“…Although toxic effects of this drug were unexpected, because the selenium in ebselen is not released, is not bioavailable and ebselen metabolites are excreted in bile and urine, 29 experimental evidence shows that ebselen causes cell death in several cancer cell types, including AR42J cells. 8,9 The concentrations of ebselen that we have employed fall within the range of concentrations employed by others, which vary between 1 and 40 μM, and have reported protective effects of the compound. 30,31 However, previous studies carried out in our laboratory have shown that ebselen may cause damage to the cells.…”
Section: Effect Of Ebselen On Mitogen-activated Protein Kinasesmentioning
confidence: 86%
“…6 However, deleterious effects of ebselen have been also reported. Ebselen sensitizes glioma cells to TNFalphainduced apoptosis, 7 induces cell death in AR42J cells, 8 induces apoptosis in human multiple myeloma cell lines, 9 increases the toxicity of copper in astrocytes, 10 and inhibits hepatitis C virus NS3 helicase binding to nucleic acid and prevents viral replication. 11 Moreover, anti-neoplastic properties of ebselen in pancreatic and renal cancer cell lines have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Free radicals such as ROS and NO are known to induce oxidative stress, subsequently impairing mitochondrial function [21]. Recent studies have demonstrated that the production of ROS increases, as followed by Bax translocation, and then triggers the cell apoptosis [22]. A strong…”
Section: Lps Accelerates Srm 2786-induced Cell Apoptosis In 16hbe Cellsmentioning
confidence: 99%
“…Then it causes the release of cytochrome c. Cytochrome c is released into the cytosol and activates a family of caspases. Then a series of cascade reactions are triggered [17][18][19]. Studies have shown that the increased production of reactive oxygen species (ROS) also induces a decrease in the mitochondrial membrane potential, followed by the release of cytochrome c, which ultimately leads to apoptosis [20,21].…”
Section: Introductionmentioning
confidence: 99%